The application of Fuzzy logic for managerial decision making processes : latest research and case studies - Meier, Andreas, 1951-; Portmann, Edy; Stoffel, Kilian; Terán Tamayo, Luis Fernando, 1979- (Springer, 2017)
This book addresses the latest research and applications of fuzzy management methods for business decisions. It showcases a broad set of applications and discusses topics such as measures for the quality of analytics outcomes in big data environments; how fuzzy management methods support the inclusion of human thinking and human behavior in decision making processes; how to generate better results with fuzzy management methods in cases of imprecise information; new personalization concepts enabled by fuzzy logic for the offering of customized products and services especially in the electronic market; and lastly the application of fuzzy analysis for executives using natural rather than computer language. The combination of research papers and case studies makes it a valuable resource both for researchers and practitioners in the digital economy.
Keywords: Management -- Mathematical models.; Decision making -- Mathematical models.; Fuzzy logic.; elektronické knihy; electronic books